2001
DOI: 10.7601/mez.52.43
|View full text |Cite
|
Sign up to set email alerts
|

Migration of the roof rat, Rattus rattus, between houses and paddy fields in Indonesia

Abstract: The infiuence of paddy field development on the population of the roof rat, Rattus rattus, was assessed in West Timor (August 1998 and 1999, dry season; February 2000, wet season) and Central Sulawesi (August 1998, wet season), Indonesia, In West Timor, the rats foraged houses and their vicinities but not paddy fields in the early vegetative stage either in August or in February, In West Timor in August, 48% of the sampled rats was estimated to have been born during the harvest-time in or just after the wet se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…It was reported that the roof rat was less reproductive with falling temperature 21 . Since the roof rat is a commensal species, it tend to move from fields to homes after the harvest season 26 . Therefore, it was suggested that the cause of rat-damage in winter was not the rapidly proliferating number of rats in the stock yard but the masking situation by snow.…”
Section: Effects Of Spacious Layout In Farm Conditions (Experiments 3)mentioning
confidence: 99%
“…It was reported that the roof rat was less reproductive with falling temperature 21 . Since the roof rat is a commensal species, it tend to move from fields to homes after the harvest season 26 . Therefore, it was suggested that the cause of rat-damage in winter was not the rapidly proliferating number of rats in the stock yard but the masking situation by snow.…”
Section: Effects Of Spacious Layout In Farm Conditions (Experiments 3)mentioning
confidence: 99%